Global Proteomic Response of Caenorhabditis elegans Against PemKSa Toxin - Mir, Dilawar Ahmad; Balamurugan, Krishnaswamy (Frontiers in Cellular and Infection Microbiology, 2019)
Bacterial exotoxins are capable of causing infection by promoting cell and tissue damages through disabling the invading host immune system. However, the mode of action by which toxins modulate host cell death and immune system are not completely understood. The nematode, Caenorhabditis elegans has been used as an attractive model host for toxicological studies. The present study was undertaken to assess the impact of Staphylococcus aureus toxin (PemK) on the host C. elegans proteome. Our proteomic data obtained through LC-MS/MS, subsequent bioinformatics and biochemical analyses revealed that in response to PemKSa a total of 601 proteins of C. elegans were differentially regulated. The identified proteins are mainly participating in ATP generation, protein synthesis, lipid synthesis, cytoskeleton, heat shock proteins, innate immune defense, stress response, neuron degeneration and muscle assembly. Current findings suggested the involvement of several regulatory proteins that appear to play a role in various molecular functions in combating PemKSa toxin-mediated microbial pathogenicity and/or host C. elegans immunity modulation. The results provided a preliminary view of the physiological and molecular response of a host towards a toxin and provided insight into highly complex host-toxin interactions.